Testing analytic techniques - Hill, Martin (Cranfield University, 2021)
We usually have too little time and too much data to assess, communicate and act before the situation changes. The relevant data “SUCs”: it is Scattered across different sources, Unreliable, and Cluttered by irrelevant data [1]. There is too much for one brain to cope with, so we work as teams – our cognition is distributed across individuals and groups – with all the extra time demands and cognitive loads that brings.
Reproduced with permission kindly granted by The Cabinet Office. (c) The Author